2017
DOI: 10.5114/aoms.2015.52104
|View full text |Cite
|
Sign up to set email alerts
|

Blood groups and acute aortic dissection type III

Abstract: IntroductionAcute aortic type III dissection is one of the most catastrophic events, with in-hospital mortality ranging between 10% and 12%. The majority of patients are treated medically, but complicated dissections, which represent 15% to 20% of cases, require surgical or thoracic endovascular aortic repair (TEVAR). For the best outcomes adequate blood transfusion support is required. Interest in the relationship between blood type and vascular disease has been established. The aim of our study is to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Previously, Fatic et al showed that a higher proportion of patients diagnosed with AAA had blood group O when compared with blood donors in the normal population, 11 whereas Viklander et al 9 could not find any association between blood groups and the risk of developing AAA or AAA rupture. It has been reported that non-O blood groups (ie, blood groups A, B and AB) are associated with significantly higher risk of VTE and cardiovascular disease, including myocardial infarction, peripheral vascular disease and cerebrovascular stroke.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previously, Fatic et al showed that a higher proportion of patients diagnosed with AAA had blood group O when compared with blood donors in the normal population, 11 whereas Viklander et al 9 could not find any association between blood groups and the risk of developing AAA or AAA rupture. It has been reported that non-O blood groups (ie, blood groups A, B and AB) are associated with significantly higher risk of VTE and cardiovascular disease, including myocardial infarction, peripheral vascular disease and cerebrovascular stroke.…”
Section: Discussionmentioning
confidence: 97%
“…[4][5][6][7][8] Few studies have examined the association between ABO blood group and aortic disease. [9][10][11] In an analysis of 504 patients with abdominal aortic aneurysm (AAA), Viklander et al did not find a significant difference in distribution of blood groups between patients with AAA or ruptured AAA compared with a population-based control group. 9 Fatic et al on the other hand, demonstrated that a significantly higher proportion of patients with AAA had blood group O compared with a control group consisting of blood donors from the general population of Montenegro.…”
Section: Introductionmentioning
confidence: 99%
“…To be noted, this relationship has also been investigated in two other studies. Nikola et al designed a case-control study involving 115 patients with type III AD and revealed no significant difference in mortality between various blood groups [20].…”
Section: Discussionmentioning
confidence: 99%
“…To be noted, this relationship has also been investigated in two other studies. Nikola et al designed a case–control study involving 115 patients with type III AD and revealed no significant difference in mortality between various blood groups [ 20 ]. A more recent study concerning the surgical prognosis of AD, by Nozohoor et al, included a larger population from The Nordic Consortium for Acute Type A Aortic Dissection database [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The demand for primary TKA is predicted to grow by 673%, to reach 3.48 million by 2030 in the United States. Although the operation has good outcomes and is generally well tolerated, the complications of blood transfusion are also severe, including infection, transfusion-related liver damage, hemolysis, immune suppression, prolonged rehabilitation duration and allergic reactions [5], and blood loss is a major concern both during and after TKA surgery [6].…”
Section: Introductionmentioning
confidence: 99%